CHITOSAN NANOBUBBLES DEVELOPMENT AND EVALUATION FOR THE DELIVERY OF SUNITINIB-AN ANTICANCER AGENT - KUMAR M., KISHORE; PRAKASH D., JAYA; RAO V. V., BASAVA (International Journal of Applied Pharmaceutics, 2022)
Objective: In the current study, we introduced a novel method for creating Sunitinib nanobubbles by incorporating it into chitosan-shelled nanobubbles. Methods: The Design Expert® programme randomly assigned around 13 experiments, and multiple regression analysis was used to statistically examine the data. The effect of the amount of sunitinib, amount of chitosan, amount of Epikuron 200, amount of palmitic acid and stirring speed, on percent encapsulation efficiency and drug load while maintain minimum particle size of nanobubbles as considered through a definitive screening plan. By placing limitations on the response parameters, the optimum formulation was created using a numerical optimization approach. The three improved formulations (Batch1 through Batch3) were assessed. Results: The findings show that the nanobubbles particle size of 78.56-82.42 nm with an encapsulation efficiency of 68.48-69.56 % and loading capacity of 23.88-25.02%. The quantity of sunitinib released from nanobubbles was much larger (96.52 percent) than that from the sunitinib solution within 24 h, according to an in vitro release profile of the medication using ultrasonography. The hemolytic activity of the blank nanobubbles and sunitinib-loaded nanobubbles was measured to assess their safety up to a concentration of 10 mg/ml. With erythrocytes, drug-loaded nanobubbles had a good safety profile. FTIR, DSC studies indicated no chemical interactions, TEM images revealed nanobubbles size of 70-100 nm and stability studies shows no significant changes. Conclusion: For contrast-enhanced tumour imaging and subsequent therapeutic administration, nanobubbles were found to be superior.